2023
DOI: 10.1097/scs.0000000000009782
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell Transcriptomics Reveals Activation of Macrophages in All-trans Retinoic Acid (atRA)-induced Cleft Palate

Binqing Wang,
Meng Xu,
Jingjing Zhao
et al.

Abstract: Cleft palate is among the most common birth defects with an impact on swallowing and speaking and is difficult to diagnose with ultrasound during pregnancy. In this study, we systematically capture the cellular composition of all-trans retinoic acid (atRA)-exposed and normal embryonic gestation 16.5 days mouse palate by the single-cell RNA sequencing technique. The authors identified 14 major cell types with the largest proportion of fibroblasts. The proportion of myeloid cells in atRA-exposed palate was marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(82 reference statements)
0
0
0
Order By: Relevance
“… 82 The recent single-cell RNA-seq and single-cell multiome studies in mice also showed that Fos and Jun were involved in secondary palate development 54 and all- trans retinoic-acid-induced CP. 83 …”
Section: Discussionmentioning
confidence: 99%
“… 82 The recent single-cell RNA-seq and single-cell multiome studies in mice also showed that Fos and Jun were involved in secondary palate development 54 and all- trans retinoic-acid-induced CP. 83 …”
Section: Discussionmentioning
confidence: 99%